Digital transformation of public relations and communication departments of a sample of spanish companies - Cuenca-Fontbona, Joan (2020)
The goal of this article is to analyze the degree of maturity in the digital transformation of the public relations and communication departments of the companies with the highest turnover that belong to the Spanish Association of Communication Directors-Dircom by applying the model for digital transformation proposed by Westerman, Bonnet and McAfee (2012), based on the vectors of leadership and digital capacity. For this purpose, a questionnaire was sent to those responsible for communication of this type of companies. Our results identify that 73.6% of the communication departments are at an advanced stage of this transformation, conditioning cultural changes to corporate governance, the demand for new profiles, the reorganization of work, and focusing on areas where there is an improvement that maximizes the return of resources invested. 85% of these departments have an integral vision of digital communication, although they recognize that they must automate many of their processes. Keywords: Digital Transformation, Digital Communication, Information Technology, Public Relations, Communication Departments, Spanish Corporations.